2019
DOI: 10.12688/f1000research.20062.1
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of nicotine exposure: A narrative review of the scientific literature

Abstract: The emergence of new tobacco heating products and electronic nicotine delivery systems (ENDS) is changing the way humans are exposed to nicotine. The purpose of this narrative review is to provide a broad overview of published scientific literature with respect to the effects of nicotine on three key health-related areas: 1) cardiovascular risk, 2) carcinogenesis and 3) reproductive outcomes. These areas are known to be particularly vulnerable to the effects of cigarette smoke, and in addition, nicotine has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 130 publications
0
5
0
Order By: Relevance
“…One of the substantial pieces of evidence that indicate the health risk related to the use of ENDS in the framework is that among experienced adult ENDS users, nicotine intake can be comparable to that from combustible tobacco cigarettes. Nicotine contributes to smoking initiation and subsequent addiction, and exposes the user to cardiovascular events through atherosclerosis [ 22 27 ] , especially in persons with underlying coronary artery disease [ 23 , 24 ] . Moreover, preliminary findings show that nicotine, especially through its derivates when smoked or consumed orally, may contribute to cancer development by stimulating certain key processes [ 28 ] , including the activation of nicotine acetylcholine receptors.…”
Section: Introductionmentioning
confidence: 99%
“…One of the substantial pieces of evidence that indicate the health risk related to the use of ENDS in the framework is that among experienced adult ENDS users, nicotine intake can be comparable to that from combustible tobacco cigarettes. Nicotine contributes to smoking initiation and subsequent addiction, and exposes the user to cardiovascular events through atherosclerosis [ 22 27 ] , especially in persons with underlying coronary artery disease [ 23 , 24 ] . Moreover, preliminary findings show that nicotine, especially through its derivates when smoked or consumed orally, may contribute to cancer development by stimulating certain key processes [ 28 ] , including the activation of nicotine acetylcholine receptors.…”
Section: Introductionmentioning
confidence: 99%
“…An association between cigarette smoking and increased risk of CVD is well-established, but it is not clear whether this association is mediated by exposure to nicotine and/or to other constituents found in cigarette smoke (6). Both laboratory and clinical studies in humans have shown that nicotine stimulates the sympathetic nervous system, resulting in transient increases in heart rate and blood pressure, as well as changes in other cardiovascular parameters (7)(8)(9)(10)(11)(12)(13). However, there is evidence to suggest that these effects are more pronounced in response to exposure to components related to the use of combustible tobacco products than to nicotine alone (6,10,14).…”
Section: Introductionmentioning
confidence: 99%
“…Smoking during pregnancy is associated with different serious adverse obstetric and neonatal outcomes [1,2]. These health risks to the developing fetus will create problems that will persist long after delivery [3].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of NRT in the general population of smokers is well studied; however, there is limited evidence on the efficacy and safety of these medications when used during pregnancy [8]. NRT is the most studied pharmacotherapy used for smoking cessation among pregnant women [2]. Nicotine acts on cholinergic nicotinic-type acetylcholine receptors (nAChr), such as A4 β2, located in the membranes of neurons in the ventral tegmental area of the midbrain, and it leads to increased dopamine release in the nucleus accumbens and is responsible for the feeling of reward.…”
Section: Introductionmentioning
confidence: 99%